Microneedling on the external female genitalia's flaccidity in patients with Ehlers‐Danlos: Case report. (7th February 2019) - Gomes, Tâmara; Baqueiro, Priscilla; Oliveira, Caroline; Alves, Rafael; Lordelo, Patrícia
Summary: Introduction: The Ehlers‐Danlos Syndrome (EDS) can presentis a reduction in fibroblast proliferation and collagen production. Microneedling a minimally invasive technique that through mechanical stimulus there is incentive to the production of collagen and elastin. Objective: Present a case study in a patient with EDS complaining of flaccidity on large genital labia, using microneedling as a therapeutic proposal. Methodology: A 36‐year‐old female with EDS type III. The external genitalia showed tissue flaccidity associated with hyperchromia. Microneedling was performed with 0.5 mm needles and the cosmetology was used soon after the application. The level of pain was questioned to the patient through a Likert scale. The clinical response to treatment was evaluated through self‐report, visual analogue scale and analysis of photographic images. Five other people evaluated the results through before and after images. Results: Microneedle was shown to be bearable in relation to pain and associated with cosmetology for tissue flaccidity due to EDS in the genital region proved to be very satisfactory for the patient, as well individuals who evaluated the comparative image. Conclusion: Microneedle associated with cosmetology may be a new option for studies on skin flaccidity treatments on individuals with EDS and for treatments of genital hyperchromias